The Inter-Institutional Consortium (I-IC) processing center, 1981-1991 a performance audit - Garcia, Perla T.; Faderon, Rosalie B.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1993)
This study determined the efficiency and effectiveness of the Inter-Institutional Consortium (I-IC) Processing Center in its ten years of operation, (1981-1991), in terms of its implementing processes and products within its context and input components. The I-IC Processing Center is a cooperative centralized cataloging project of libraries of five institutions of higher learning, namely: De La Salle University, St. Paul College, Manila, and St. Scholastica's College.
Analysis of extant documents and the descriptive survey method were used to gather data. The efficiency of the Center was determined by comparing the completion rate of cataloging output with the required monthly cataloging output of five hundred book titles. The general physical flow of the processing and the specific cataloging procedures were described and illustrated in flowcharts.
The effectiveness of the Center was measured according to the extent of the accomplishment of its objectives expressed in the following criteria: 1) comparative ratio of cataloging output of the Center with the cataloging output of the individual library; 2) quality of cataloging output in terms of completeness and consistency with AACR2 and Library of Congress Classification Scheme; 3) income; and 4) the extent of use of the union catalog and cataloging tools by the cataloging staff of the member libraries.
Among the findings of the study were: 1. The Center was found inefficient in the delivery of its cataloging service as indicated by the slow turnaround time of books processed. It was able to process on the average 149.91 titles a month against the target output of 500 titles a month. 2. Overall, the preparation of cataloging output of the Center compared with the cataloging output of the consortium libraries is 18 percent with the highest cataloging support given to PCU Library. 3. The Center was found effective in performing its cataloging function as reflected by the great number of quality catalog records produced. Only ten percent of the records was found to be incomplete and 15.9 percent was found inconsistent. 4. The budget performance of the Center showed its incapacity to sustain itself in its cataloging function. A total deficit of P13,275.32 was accumulated by the end of the tenth year of operation of the Center. 5. Despite availability of the union catalog either in card format and computerized format, access to and use of it by the cataloging staff of the consortium was not fully maximized.
Typescript
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Cataloging cooperative; Inter-Institutional Consortium (IIC) Processing Center; Library consortia See Library cooperation; Library cooperation